Preparing South African Foundation Phase Preservice Teachers to Teach Reading for Meaning - Dlamini, Nosisi Percis (International Journal of Language and Literary Studies, 2022)
Scholars have widely documented the current reading crisis in South Africa. This crisis has drawn attention to the need for adequately prepared teachers to teach reading for meaning, particularly in the Foundation Phase classroom. However, little is known about how South African teacher education institutions prepare preservice Foundation Phase teachers to teach reading for meaning. This article addresses this gap by offering recommendations on how South African teacher education institutions can prepare preservice teachers to teach reading for meaning in the Foundation Phase classrooms. The article argues that there is an urgent need for South African teacher education institutions to rethink their curricula to prepare teachers to teach reading for meaning in the South African Foundation Phase classroom. By focusing on preparing Foundation Phase teachers to teach reading for meaning, the article seeks to contribute to a reconceptualization of the content and structure of the South Foundation Phase teacher education curriculum. It also lays the groundwork for further research on the preparation of South African Foundation preservice teachers to teach reading for meaning.